Revised Ordinances of the City of Fort Worth, Texas, 1873-1884, at 113-14, An Ordinance defining and punishing affrays and Disturbances of the Peace, § 2 (1885) - (:unkn) unknown (General Publisher, 1879)
If any person shall go into any public place, or into or near any private house, or along any public street or highway near any private house, and shall use loud and vociferous, or obscene, vulgar, or indecent language, or swear or curse, or expose his person, or rudely display any pistol or other deadly weapon in such public place, or upon such public street or highway, or near such private house, in a manner calculated to disturb the inhabitants thereof, he shall be fined in a sum not exceeding one hundred dollars.
--
Keywords: BRANDISHING